Vandalism and Anti-Social Behaviour - Long, Matt. author. aut Link
VI, 258 p.
Keywords: Vandalism and Anti-Social Behaviour forwards a new typology of vandalism. The authors argue that in order to fully understand vandalism and anti-social behaviour, a culturally criminological perspective should be fostered, which accounts for the emotional and experiential aspects of crime.